Carbonized Aramid Fiber as the Adsorbent for In-Tube Solid-Phase Microextraction to Detect Estrogens in Water Samples - Xiaoxiao Zhu; Yijun Zhang; Pengfei Liu; Xiuzhi Bai; Na Chen; Yuping Zhang (Journal of Chemistry)
Carbonized aramid fiber was prepared as a new type of adsorbent for in-tube solid-phase microextraction. The surface structure, chemical composition, and graphitization degree of the resulted fiber was determined and characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, and Raman spectrometry. The prepared fiber was packed in a stainless-steel tube instead of the sample loop of a six-port and tested for the extraction of five environmental estrogen hormones coupled with high-performance liquid chromatography. Several parameters affecting the estrogens’ extraction including the sampling volume, sampling rate, NaCl content, and desorption time were investigated in detail. The extraction tube with carbonized aramid fiber exhibited remarkable extraction performance towards five estrogen targets. The analysis method was established, and it exhibited a wide linear range (0.5–10.0 μg/L) with good linearity (correlation coefficient ≥0.9906), low limits of detection (0.011–0.13 μg/L), and high enrichment factors (178–1335) for the five analytes. Relative standard deviations (n = 3) for intraday (≤4.8%) and interday (≤4.0%) tests indicated that the extraction material had satisfactory repeatability. Bisphenol A released from a polycarbonate (PC) bottle was quantitatively detected with a concentration of 8.3 μg/L. The relative recoveries spiked at 5 and 10 μg/L were investigated, and the results were in the range of 74.3–121% for real water samples.